2012
DOI: 10.1503/cjs.018310
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the effectiveness of prophylactic antibiotics in the prevention of postoperative complications after tension-free hernioplasty

Abstract: Background: Previous reviews of the effectiveness of antibiotic prophylaxis for elective inguinal hernia repair were not conclusive owing to the limited number of patients enrolled in randomized controlled trials (RCTs). However, since new RCTs involving patients undergoing tension-free hernioplasty have been published in recent years, we performed a new meta-analysis to evaluate the effectiveness of antibiotic prophylaxis in the prevention of postoperative complications after this procedure. Methods:We perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…A separate meta-analysis, also published in 2012, focussed purely on inguinal hernia repair with mesh and included six of the 11 RCTs identified by the Cochrane review. This analysis concluded that there was a significant benefit associated with prophylaxis [7]. One further RCT has recently been reported: this small study found no significant difference in risk of infection between use of prophylaxis and placebo [8].…”
Section: Introductionmentioning
confidence: 99%
“…A separate meta-analysis, also published in 2012, focussed purely on inguinal hernia repair with mesh and included six of the 11 RCTs identified by the Cochrane review. This analysis concluded that there was a significant benefit associated with prophylaxis [7]. One further RCT has recently been reported: this small study found no significant difference in risk of infection between use of prophylaxis and placebo [8].…”
Section: Introductionmentioning
confidence: 99%
“…The Lichtenstein tension-free hernia repair gained broad acceptance especially in the last decade due to its being an easily applied technique with low recurrence rates (1). However the polypropylene mesh used in this technique has given rise to complications like foreign body reaction, "Surgical Site Infection (SSI)", seroma, adhesion, graft migration, graft rejection and chronic pain (2)(3)(4). All these probable complications result in an increase in morbidity, length of hospital stay and cost.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis concluded that there was a significant benefit associated with prophylaxis. 10 Another RCT has found no significant difference in risk of infection between use of prophylaxis and placebo. 11 Because of the differing conclusions from various studies, the clinical guidelines vary.…”
Section: Discussionmentioning
confidence: 99%